Host cell protein detection gap risk mitigation: quantitative IAC-MS for ELISA antibody reagent coverage determination. Issue 1 (1st January 2021) - Waldera-Lupa, Daniel M.; Jasper, Yvonne; Köhne, Pia; Schwichtenhövel, Ronja; Falkenberg, Heiner; Flad, Thomas; Happersberger, Peter; Reisinger, Bernd; Dehghani, Alireza; Moussa, Roland; Waerner, Thomas
ABSTRACT: Host cell proteins (HCPs) must be sufficiently cleared from recombinant biopharmaceuticals during the downstream process (DSP) to ensure product quality, purity, and patient safety. For monitoring of HCP clearance, the typical method chosen is an enzyme-linked immunosorbent assay (ELISA) using polyclonal anti-HCP antibodies obtained from an immunization campaign. This polyclonal reagent is a critical factor for functionality and confidence of the ELISA. Therefore, it is important to ensure that the pool of ELISA antibodies covers a broad spectrum of the HCPs that potentially could persist in the final drug substance. Typically, coverage is determined by gel-based approaches. Here, we present a quantitative proteomics approach combined with purification of HCPs by immunoaffinity chromatography (qIAC-MS) for assessment of ELISA coverage. The cell culture fluid (CCF) of a mock fermentation and a recombinant monoclonal antibody product were characterized in detail to investigate whether the HCPs used for immunization of animals accurately represent HCPs that are relevant to the process. Using the qIAC-MS approach, the ELISA antibody coverage was determined for mock fermentation and product CCF, as well as several different DSP intermediates. Here, the use of different controls facilitated the identification and quantification of HCPs present in the polyclonal reagent and those that nonspecifically bound to IAC material. This study successfully demonstrates that the described qIAC-MS approach is not only a suitable orthogonal method to commonly used 2D SDS-PAGE-based analysis for evaluating ELISA antibody coverage, but that it further identifies HCPs covered as well as missed by the ELISA, enabling an improved risk assessment of HCP ELISA.